Физиотерапия и физиопрофилактика болезней животных: Справ. изд. / А. Д. Белов, И. М. Беляков, В. А. Лукьяновский - Белов Алексей Дмитриевич (Колос, 1983)
Экземпляры: ф.10 (20190906) / Инвентарный номер: 6598 / Цена: 0.60 / Авт.знак: Б 43 / ГРНТИ: 68.41 / ББК: 48